2012
DOI: 10.1111/j.1095-8649.2011.03189.x
|View full text |Cite
|
Sign up to set email alerts
|

Are phenotypic traits useful for differentiating among a priori Coregonus taxa?

Abstract: A key for three putative species apparently found in three geographic areas, i.e. Coregonus clupeoides (in Scotland), Coregonus stigmaticus (in England), and Coregonus pennantii (in Wales) given in a recent review was tested quantitatively using 544 individuals from nine populations. The classification success of the key was very low (27%). It was concluded that there is currently no robust evidence for the recognition of the three putative species. Furthermore, the use of phenotypic characters alone to distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 41 publications
1
23
1
1
Order By: Relevance
“…Coregoniden populaties bevinden zich sinds de laatste ijstijden in een snel proces tot soortvorming ('adaptive radiation'), enerzijds door isolatie en herkolonisatie in tal van koude meren en rivieren en anderzijds door een veranderende omgeving. Of en wanneer een populatie coregoniden tot een aparte soort moet worden beschouwd is vaak controversieel en tot op zekere hoogte subjectief (Hansen et al 2008 (Østbye et al 2005, Hansen et al 2008, Etheridge et al 2012.…”
Section: Figuur 1 Het Historische Verspreidingsgebied Van Houtingen unclassified
“…Coregoniden populaties bevinden zich sinds de laatste ijstijden in een snel proces tot soortvorming ('adaptive radiation'), enerzijds door isolatie en herkolonisatie in tal van koude meren en rivieren en anderzijds door een veranderende omgeving. Of en wanneer een populatie coregoniden tot een aparte soort moet worden beschouwd is vaak controversieel en tot op zekere hoogte subjectief (Hansen et al 2008 (Østbye et al 2005, Hansen et al 2008, Etheridge et al 2012.…”
Section: Figuur 1 Het Historische Verspreidingsgebied Van Houtingen unclassified
“…However, the freshwater figure is inflated by a considerable number of introduced species (primarily from Continental Europe and North America) which are of relatively low abundance. As discussed by Etheridge et al [14], the freshwater figure has also been raised by recent contentious taxonomic revisions which have split some former species into a number of "new" species. In the view of many authorities such as Maitland [15] and certainly in terms of practical implications for fisheries and their management, the effective species number for UK fresh waters is somewhere between 50 and 60 fish species.…”
Section: The Fishesmentioning
confidence: 99%
“…Freyhof and Schöter (2005) suggested that the North Sea houting was confined to the region of the Rhine River and is now extinct, a conclusion that has been adopted by the International Union for the Conservation of Nature. However, the study of Freyhof and Schöter (2005) focused on morphological traits that are highly homeoeplastic in whitefish (Bernatchez et al 1996;Østbye et al 2005Etheridge et al 2012). Therefore, the conclusion of extinction is considered disputable (Jacobsen et al 2012).…”
Section: Introductionmentioning
confidence: 99%